Outpatient’s Satisfaction Analysis of Pharmaceutical Service in Pharmacy Installation in Reksodiwiryo Hospital Padang - Mela Aryati; Deddy Almasdy; Husna Yetti; Aldino Desra (Disease Prevention and Public Health Journal, 2022)
Background: Currently, Indonesia's health development began to emphasize improving the quality of health care, where service quality should be oriented to customer satisfaction to continue to exist during global competition. This study aims to determine the level of satisfaction of outpatients at the depot pharmacy installation at Reksodiwiryo Padang Hospital. Method: This research is a cross-sectional study design. Sampling was carried out from February to March 2022 with a sample of 425 people using the accidental sampling technique. Data were analyzed using univariate and Cartesian diagrams. The sample is outpatient in pharmacy installation Reksodiwiryo Padang. Result: Patients are dissatisfied with all dimensions, there is the tangibles dimension (70.6%), the reliability dimension (66.1%), the responsiveness dimension (57.4%), the assurance dimension (49.6%), and dimensions of empathy (38.8%). In the Cartesian diagram analysis, the most questions were category B, then C, A and finally D. There are two attributes involved in quadrant A, there is the punctuality of the officers in serving and the drug items are always available. Conclusion: Most of the respondents expressed dissatisfaction with the services received at the pharmacy installation of the Reksodiwiryo Hospital. The hospital management can refer to the cartesian diagram analysis to prioritize better improvement.